A Health Records Review of Outpatient Referrals from the Emergency Department - Nicholas Prudhomme; Edmund S. H. Kwok; Laura Olejnik; Shannon White; Venkatesh Thiruganasambandamoorthy (Emergency Medicine International)
Objectives. Many patients discharged home from the emergency department (ED) require urgent outpatient consultation with a specialty service. We sought to identify the best- and worst-performing services with regard to time to outpatient consultation, the proportion of patients lost to follow-up, the rate of related return ED visits prior to consultation, and common strategies used by our top-performing clinics. Methods. We conducted a health records review of The Ottawa Hospital ED visits during four 1-week periods. All consecutive adult outpatient consultation requests were included for chart review and were followed up to 12 months. Outcome measures included demographics, referral attendance rates, incomplete referrals, return ED visits, and time intervals. Services with at least 15 consultation requests were included for data analysis and qualitative mapping of their referral processes. Results. Of the 963 patients who met inclusion criteria, 803 (83.4%) attended their appointment, while 160 (16.6%) were lost to follow-up. The overall median time to successful consultation was 9 days (IQR = 2–27). 92 (9.6%) patients returned to the ED with a related complaint. The top-performing clinics included ophthalmology, orthopedics, and thrombosis (median = 1, 8, 1 days; incomplete consultation = 3%, 4%, 6%; return ED visits = 0%, 6%, 2% respectively). The bottom-performing clinics included otorhinolaryngology, neurology, and gynecology (median = 47, 39, 27 days; incomplete consultation = 50%, 41%, 37%; return ED visits = 11%, 15%, 26%, respectively). Processes incorporated by top-performing clinics included reserving appointment slots for emergency referrals, structured referral forms, and centralized booking. Conclusions. We found a substantial variability in both the waiting times and reliability of outpatient referrals from the ED. Top-performing clinics incorporate common referral processes.